Efektivitas Penggunaan Birth Ball Terhadap Intensitas Nyeri Persalinan : Systematic Literature Review - Nova Avianti Rahayu; Jumiati; Ayu Septiani (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
The birth process begins with uterine contractions which cause dilatation and thinning of the cervix and ischemia of the uterus, giving rise to a painful response. Labor pain needs to get good treatment and not cause complications that can interfere with labor. Birth ball is a method to help mothers reduce pain during labor which encourages the mother's strong energy needed during childbirth. The purpose of this review is to find a research method using a systematic literature review approach and there are eight stages used in this review, namely identifying midwifery problems, priority problems and research questions, primary and secondary data frameworks, identification of relevant studies, prism flow diagrams, critical appraisal, data analysis and data extraction. This review uses 2 databases with a period from 2010-2020. The total articles obtained were 713 articles, 12 articles were selected for review. Several articles compared the intensity of labor pain in the intervention group using birth balls and without intervention and it was found that the use of birth balls was an effective non-pharmacological pain management method for reducing labor pain. The conclusion of this study is that the use of a birth ball is effective in reducing pain intensity during the first stage of labour.